AKI and Its Relation with Outcome in Patients with COVID-19 - Faiza Nafees Khan, Quratulain Khan, Jamil Muqtadir Bhatti, Shazia Hashmat, Sadaf Fatima, Sumbal Nasir Mahmood, Kevin Joseph Jerome Borges (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Coronavirus disease 2019 (COVID-19) is currently spreading fast around the world. The rate of acute kidney damage (AKI) in patients hospitalized with Covid-19, as well as the outcomes related with it, are unknown. The goal of this study was to see if having acute kidney damage (AKI) increased the risk of severe infection and death in COVID-19 patients. It also described the symptoms, risk factors, and outcomes of AKI in Covid-19 patients. Material and Methods: We undertook a retrospective cohort from June 2020 and March 2021 to examine the connection between AKI and patient outcomes COVID-19. Results: The most common comorbid condition was hypertension and diabetes followed by chronic kidney disease and ischemic heart disease. Most of the patients who required low dose oxygen with nasal prongs, face masks, or rebreathing masks were in control groups (76.2% vs. 50.6%; p <.001). More patients in AKI group needed non-invasive ventilation and invasive mechanical ventilation compared to control group (33.8% vs. 19.9%; p .001, 15.6% vs. 3.9%; p <.001 respectively. Patients in the AKI group had higher levels of C-reactive protein, lactate dehydrogenase, D-dimer, and serum. Of 145 patients who developed AKI, 29 (20%) needed hemodialysis. Of 29 patients who needed hemodialysis, 18 (62%) expired. A higher number of patients in the control group were discharged than patients in the AKI group (82.1% vs. 56.9%; p <.001). One hundred five patients were expired, with higher mortality in the AKI group (41.7% vs. 12.4%; p <.001). Conclusion: COVID-19 patients admitted to the hospital, AKI is associated with a shockingly high fatality rate. Keywords: chronic kidney disease, ischemic heart disease, lactate dehydrogenase.